Chloroquine inhibits autophagic flux by decreasing autophagosome-lysosome fusion. Issue 8 (3rd August 2018) - Mauthe, Mario; Orhon, Idil; Rocchi, Cecilia; Zhou, Xingdong; Luhr, Morten; Hijlkema, Kerst-Jan; Coppes, Robert P.; Engedal, Nikolai; Mari, Muriel; Reggiori, Fulvio
ABSTRACT: Macroautophagy/autophagy is a conserved transport pathway where targeted structures are sequestered by phagophores, which mature into autophagosomes, and then delivered into lysosomes for degradation. Autophagy is involved in the pathophysiology of numerous diseases and its modulation is beneficial for the outcome of numerous specific diseases. Several lysosomal inhibitors such as bafilomycin A1 (BafA1 ), protease inhibitors and chloroquine (CQ), have been used interchangeably to block autophagy in in vitro experiments assuming that they all primarily block lysosomal degradation. Among them, only CQ and its derivate hydroxychloroquine (HCQ) are FDA-approved drugs and are thus currently the principal compounds used in clinical trials aimed to treat tumors through autophagy inhibition. However, the precise mechanism of how CQ blocks autophagy remains to be firmly demonstrated. In this study, we focus on how CQ inhibits autophagy and directly compare its effects to those of BafA1 . We show that CQ mainly inhibits autophagy by impairing autophagosome fusion with lysosomes rather than by affecting the acidity and/or degradative activity of this organelle. Furthermore, CQ induces an autophagy-independent severe disorganization of the Golgi and endo-lysosomal systems, which might contribute to the fusion impairment. Strikingly, HCQ-treated mice also show a Golgi disorganization in kidney and intestinal tissues. Altogether, our data reveal that CQ and HCQ are not bona fide surrogates for other types of late stage lysosomal inhibitors for in vivo experiments. Moreover, the multiple cellular alterations caused by CQ and HCQ call for caution when interpreting results obtained by blocking autophagy with this drug.